The lies and fabricated arguments put forward by the Italian press for the Italian occupation of Libya in 1911 (Journal of the College of Basic Education, 2022)
This research was the result of a strenuous scientific effort that I made during my stay in Libya to teach there between the years 1997-2000, as I thought that Libyan universities depend on scientific promotion based on scientific research, as is the case in Iraqi universities, so I thought of writing a group of researches in line with the orientation of universities Scientific interest in modern Libyan history, a scientific specialist and focus on the Italian occupation of Libya.